Analisis Media Pembelajaran Berbasis Kecerdasan Buatan (AI) pada Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Rahmatika, Riska Ayu; Salam, Dudung Abdu (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the use of Artificial Intelligence (AI)-based learning media in Pancasila Education subjects in elementary schools. The study used the Systematic Literature Review (SLR) method with a qualitative descriptive approach through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) stages. Data were obtained by searching scientific articles in the Google Scholar, Garuda, SINTA, and Crossref databases. Articles were selected based on inclusion criteria, namely articles in Indonesian and English published in the 2020–2025 period, discussing the use of AI in learning, available in full text, and relevant to the research objectives. Exclusion criteria included articles that did not align with the focus of the study, were not fully available, were duplicate articles, or did not meet academic standards. Data were analyzed using thematic analysis techniques through the stages of identification, coding, grouping themes, comparison, and synthesis of previous research results. The results of the study indicate that AI-based learning media can increase learning interactivity, provide rapid feedback, assist teachers in preparing materials and assessments, and support students' critical thinking skills. However, its implementation still faces challenges such as limited teacher digital competency, infrastructure readiness, and ethical aspects of AI use. Therefore, AI needs to be utilized as a supporting medium to strengthen teachers' role in Pancasila Education learning